Plectranthias takasei, new species of anthiadine fish from southern Japan (Teleostei: Serranidae) - Gill, Anthony C.; Tea, Yi-Kai; Senou, Hiroshi (Zootaxa, 2016)
Plectranthias takasei is described from two specimens collected in Izu Oceanic Park, Sagami Bay, Honshu, Japan. It is distinguished from congeners in having the following combination of characters: dorsal rays X,15; no fleshy flaps on dorsal-fin spines; pectoral rays 13, all unbranched; branched caudal-fin rays 8 + 7; lateral line scales 28 (including intermittent and terminal pitted scales); circumpeduncular scales 12; fourth dorsal-fin spine longest; and preopercle without antrorse spines or serrations ventrally, with 2–3 weak serrations or crenulations posteriorly.